Effect of mutation of C-terminal and heme binding region of Arabidopsis catalase on the import to peroxisomes. Issue 2 (1st February 2019) - Fujikawa, Yukichi; Suekawa, Marina; Endo, Satoshi; Fukami, Youjirou; Mano, Shoji; Nishimura, Mikio; Esaka, Muneharu
ABSTRACT: We evaluated the import of Arabidopsis catalase to peroxisomes under homogenous transient expression. The amino acids at −11 to −4 from the C-terminus are necessary for catalase import. The results are in agreement with the previous work under stable expression. We first demonstrate that heme-binding sites are important for peroxisomal import, suggesting the importance of catalase folding. Abbreviations : AtCat: Arabidopsis catalase; PTS: peroxisomal targeting signal; PEX: Peroxin